INTEGRASI NILAI-NILAI FILSAFAT PENDIDIKAN ISLAM DALAM PENGEMBANGAN PEMBELAJARAN BERBASIS TEKNOLOGI - Sari, Dwi Novita; Nafisah, Fadhilah Zahrah; Jannah, Ainun Khulatifatul; Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the integration of Islamic educational philosophy values into technology-based learning to navigate digital disruption. Using a library research method, the analyzed articles were limited to those published within the last 5 years. This study analyzes the synergy between technical advancement and ethical nobility based on Islamic ontological, epistemological, and axiological foundations. The results show that the philosophy of Islamic education functions as a moral compass that positions technology as a wasilah (means) to understand sunnatullah (the laws of nature). The integration of Tawhid (the oneness of God) values fosters a sense of tawadhu (humility) in innovation, while Akhlak (morality) values frame the ethics of data usage and digital interaction. The study concludes that the synergy between digital literacy and religious understanding is crucial to developing the Ulul Albab (intellectual-spiritual elite) generation, who possess both intellectual intelligence and spiritual maturity. Consequently, this implies a need for a non-dichotomous curriculum reorientation and the transformation of educators' professionalism in creatively internalizing Islamic values into the digital ecosystem.